Gelatinase Microbial Morphology from Leather Defect - Novita Kurniawati; Yuny Erwanto; Zaenal Bachrudin; Ambar Pertiwiningrum (Buletin Peternakan, 2022)
Microbes attach in pickle leather, wet blue leather, and upper shoeleather have been identified to have positive profile to produce extracellular protease enzymes with pH values of acidic to basic on 15% gelatin and 2% commercial skimmed milk as substrates. Defective tanned leather was added to a microbial growth solution enriched with 2% gelatin substrate and incubated for 7 days at room temperature on an open rotary shaker at 120 rpm and then stored at room temperature while waiting for gelatinase testing. There were 5 morphological colonies of microbial gelatinase from defective tanned skin, all of which were white.